Reaction-diffusion model for brain spacetime dynamics - Qiang Li; Vince D. Calhoun (Biophysical Reports, 2025)
The human brain exhibits intricate spatiotemporal dynamics, which can be described and understood through the framework of complex dynamic systems theory. In this study, we leverage functional magnetic resonance imaging (fMRI) data to investigate reaction-diffusion processes in the brain. A reaction-diffusion process refers to the interaction between two or more substances that spread through space and react with each other over time, often resulting in the formation of patterns or waves of activity. Building on this empirical foundation, we apply a reaction-diffusion framework inspired by theoretical physics to simulate the emergence of brain spacetime vortices within the brain. By exploring this framework, we investigate how reaction-diffusion processes can serve as a compelling model to govern the formation and propagation of brain spacetime vortices, which are dynamic, swirling patterns of brain activity that emerge and evolve across both time and space within the brain. Our approach integrates computational modeling with fMRI data to investigate the spatiotemporal properties of these vortices, offering new insights into the fundamental principles of brain organization. This work highlights the potential of reaction-diffusion models as an alternative framework for understanding brain spacetime dynamics.